Pre‐Corrosion and Surface Treatments Effects on the Fatigue Life of AA6082 T61. Issue 10 (20th June 2013) - Abdulstaar, Mustafa; Mhaede, Mansour; Wagner, Lothar
<x xml:space="preserve">Abstract</x> Applying of surface treatments as shot peening and ball burnishing had markedly enhanced the fatigue life of AA6082 T6. Both surface treatments resulted in a surface strengthen and induced compressive residual stresses in the near surface regions. Pre‐corrosion in 3.5% NaCl solution resulted in numerous surface pits that led to degradation of fatigue life of the reference electrolytically polished conditions. These detrimental effects on fatigue life could be entirely eliminated by applying surface treatments either before or after pre‐corrosion. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>